The Abstract book of the XXI Conference of Junior Research - Jakštienė, Rita; Guogaitė, Greta; Mikučionytė, Dovilė (Vilnius University Proceedings, 2024)
The Conference of Junior Researchers in Psychology is an annual event organized by doctoral students at the Institute of Psychology, Vilnius University. The conference provides a platform for psychology students and junior researchers from universities in Lithuania and abroad to showcase their scientific work and findings. This year's conference focused on the challenges and opportunities faced by people of our time.
Keywords: psychology conference; abstract book; junior researchers